La valoración de los elementos de convicción en los delitos de evasión y su efecto jurídico en los autos de sobreseimiento dictados por la Unidad Judicial Penal con sede en el cantón Riobamba, durante el periodo de enero a septiembre del año 2014. - Usinia Iglesias, Carolina Alexandra (2016)
In Chapter I, has been developed Framework, in which consist the objectives on the basis of which the investigation was carried out, aimed at establishing, through critical study, and doctrinaire, complementary, yet legal to due legal process and its impact on the decisions of the administrative proceedings. Similarly, this chapter has been raised with the justification that the reasons I had as a researcher for conducting research shows. Chapter II focuses on the theoretical framework, covering the theoretical foundation of the research; ie, through the development of units a detailed study of the administrative responsibility of public servants in the education system, and an analysis of the Organic Law of Intercultural Education is performed to consistently study the legal effects of the transgression of due process in the administrative proceedings against the teachers of the educational system. Subsequently, in Chapter III, it sets forth the methodology for research, together with the methods and types of research that has been applied in the development of this research; and a survey form and interview that has been applied in the field research in order to obtain the most significant data supporting the hypothesis. Finally, in Chapter IV, the respective conclusions and recommendations concerning the most distinctive and momentous work of legal research aspects are presented.